Structure-oroperty pelationships in non-linear optical crystals I : The UV-Vis region - Chen, Ling; Wu, Xin-Tao (Structure and Bonding, 2012)
Wen-Dan Cheng, Chen-Sheng Lin, Wei-Long Uhang, Hao Zhang: Structural Designs and Property Characterizations for Second-Harmonic Generation Materials Fang Kong, Chuan-Fu Sun, Bing-Ping Yang, Jiang-Gao Mao: Second-order Non-linear Optical Materials based on Metal Iodates, Selenites and Tellurites Guo-Fu Wang: Structure, growth, nonlinear optics and laser properties of RX3(BO3)4 (R=Y, Gd, La; X=Al, Sc) Chaoyang Tu, Zhaojie Zhu, Zhenyu You, Jianfu Li, Yan Wang, Alain Brenier: The Recent Development of Borate SF-conversion Laser Crystal Ning Ye: Structure design and crystal growth of UV nonlinear borate materials Yi-Zhi Huang, Li-Ming Wu, Mao-Chun Hong: Cation Effect in Doped BBO and Halogen Anion Effect in Pb2B5O9X (X- = I-, Br-, Cl-)